Understanding languaculture from an indigenous Māori worldview - Berryman, Mere; Rameka, Lesley; Togo, Tracey (The Australian Journal of Indigenous Education, 2022)
This paper presents understandings from indigenous Māori kaumātua (elders both male and female) and whānau (parents and extended family members) from Aotearoa New Zealand. These people live in a close-knit hapū (subtribe) community close to an ancestral meeting space known as their marae. Their marae continues to be essential in the promotion of Māori knowledge, language and ways of being. Kaumātua and whānau recall important cultural understandings and practices from this journey. From growing up largely in te ao Māori (the Māori world) they consider “languaculture”, the inter-relationships between language, identity and culture, as foundational to their future “hope” for collective cultural strength and wellbeing. To renormalise the use of the language of their ancestors, we use many Māori words throughout. These words are italicised and translated the first time they are used.